Myofibrillar protein profile of Pectoralis major muscle in broiler chickens subjected to different freezing and thawing methods - Dauda, Adeyemi Kazeem; Mislan, Noraida; Aghwan, Zeiad Amjad Abdulrazzak; Zainal Abidin, Siti Aimi Sarah; Sazili, Awis Qurni (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The study examined the protein profile of Pectoralis major muscle in broiler chickens subjected to different freezing and thawing methods. Pectoralis major muscle was excised from the carcasses of twenty broiler chickens and split into left and right halves. The left half was subjected to slow freezing (-20°C) while the right half was rapidly frozen (-80°C). The samples were stored at their respective temperature for 2 weeks and assigned to either of tap water (27°C, 30 min), room temperature (26°C, 60 min), microwave (750W, 10 min) or chiller (4°C, 6 h) thawing. Changes in myofibrillar proteins following the thawing methods were monitored through sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The electrophoretic profile indicated differences (p < 0.05) in intensities of the components of myofibrillar proteins among the thawing methods in both slow and rapidly frozen samples. Chiller thawing had significantly higher (p < 0.05) protein concentration than other methods in rapidly frozen samples. However, in slow freezing, there were no significant differences in protein concentration among the thawing methods. In rapidly frozen samples, the protein optical densities at molecular weight of 21, 27, 55 and 151kDa in tap water, chiller and room temperature thawing did not differ (p < 0.05). Similarly, in slowly frozen samples, protein optical densities at molecular weight of 21, 27, 85 and 151 kDa were not significantly different among chill, tap water and room temperature thawing. Microwave thawing consistently caused higher protein degradation resulting in significantly lower (p < 0.05) protein quality and quantity in both freezing methods.